PENGEMBANGAN BAHAN AJAR PENDIDIKAN MATEMATIKA KELAS RENDAH MENGGUNAKAN PENDEKATAN MATEMATIKA REALISTIK - Elvi Mailani (FIP Unimed, 2020)
This study aims to develop teaching materials for low-grade mathematics education courses using a realistic mathematics approach for PGSD students at the State University of Medan. This study uses development research (Developmental Research). The subjects of this study were students majoring in elementary school teacher education (PGSD) Medan State University. In the early stages, various activities were carried out including: (1) objective analysis, (2) analysis of student characteristics, (3) analysis of lecturer needs, (4) evaluation of experts and teachers. Based on the validation results, it was found that the development of learning tools for low-grade mathematics education subjects using a realistic mathematics approach could be categorized as good and these learning devices could be used for lectures during the Covid-19 pandemic. Keywords: Realistic Mathematical Approach